Latent characteristics and preferences for income redistribution - Christian Pfarr; Andreas Schmid; Morten Raun Mørkbak (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Due to reasons such as the capacity to govern and social stability a good understanding of citizens preferences and their informal coalitions is extremely important. Because preferences for redistribution are difficult to measure identification of latent subgroups becomes non-trivial. Moreover, these groups may be determined by latent characteristics, which increase the identification problem even further. The aim of this study is to identify such groups in the context of preferences for redistribution, by adopting an inductive approach. The data for the estimation of the Willingness-To-Pay values is generated by a decision task, based on a representative sample of 1,538 German individuals. To identify the latent subgroups we investigate to which extent respondents can be grouped using latent class models thereby accounting for both observable and unobservable heterogeneity within the society. Based on the econometric analysis we can identify six social interest groups that differ regarding their preferences for redistribution and their composition. Preference regarding the overall budget for redistribution as well as regarding the different recipient groups are plausible within the political setting in Germany. This also goes for the socio-demographic determinants for group membership, which moreover match well with the current political situation in Germany.
Keywords: C93; D31; D72; 330